From structure topology to chemical composition. II. Titanium silicates : revision of the crystal structure and chemical formula of delindeite - E. Sokolova; F. Cámara (The Canadian Mineralogist, 2007)
The crystal structure of delindeite, ideally Ba2 Na2 Ti3 (Si2O7)2 O2 (OH)2 (H2O)2, a 10.6452(9), b 13.713(1), c 21.600(2) Å, β93.804(3)°, V 3146.15(5) Å3, space group C2/c, Z = 8, Dcalc 3.74 g.cm-3 from Mt. Yuksporr, Khibina alkaline massif, Kola Peninsula, Russia, has been solved by direct methods and refined to an R1 value of 6.4% on the basis of 3559 unique reflections (Fo ≥ 4σF) collected on a Bruker AXS SMART APEX diffractometer with a CCD detector and MoKα radiation. Electron-microprobe analyses gave (wt.%): SiO2 27.08, Al2O3 0.29, Nb2O5 1.98, TiO2 24.33, Fe2O3 1.07, FeO 0.40, MnO 0.19, BaO 33.20, Na2O 4.63, K2O 1.37, F 1.41, H2O 5.29 (calculated from structure refinement), O=F -0.59, total 100.65. The empirical formula is (Ba1.92 K0.08) ∑2.00 (Na1.33 K0.18 Fe2+0.05 Mn2+0.02 □1.42) ∑3.00 (Ti2.70 Fe3+0.12 Nb0.13 Al0.05) ∑3.00 (Si2O7)2 [O1.53(OH) 0.47] ∑2.00 [(OH)1.34 F0.66] ∑2.00 (H2O)1.70, Z = 8, calculated on the basis of 4 Si (apfu). The crystal structure of delindeite can be described as combination of two blocks. The first block consists of HCH sheets (H: heteropolyhedral, C: central), and it is related to the TS (titanium silicate) block in Ti disilicate minerals. In the TS block, there are seven fully occupied cation sites, four [4]-coordinated Si sites with <Si-O> 1.622 Å and three [6]-coordinated Ti-dominant sites. Two sites, M(1) and M(2), are coordinated by five 0 atoms and one OH group, <M(1,2)-O,OH)> 1.974 Å; they give Ti1.88 Nb0.07 Al0.05; the M(3) site, of composition Ti0.82 Fe3+0.12 Nb0.06, is coordinated by four O atoms and two OH groups, <M(3)-O,OH> 1.964 Å. There are four partially occupied sites: the Na(1) and Na(2) sites are occupied by Na with minor Fe2+ and Mn2+ at 70%, <Na(1,2)-O,OH,H2O> 2.31 Å; the [8]-coordinated Na(3) site of composition (Na0.70 □0.30, <Na(3)-O,H2O> 2.52 Å), and the [7]-coordinated K site of composition (K0.18 □0.82, <K-O> 2.90 Å), are at a short distance, 1.25 Å. The M(1,2) octahedra and (Si2O7) groups constitute the H ...